2007
DOI: 10.1111/j.1574-6941.2006.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Strong coupling between natural Planctomycetes and changes in the quality of dissolved organic matter in freshwater samples

Abstract: Dilution-regrowth experiments coupled to fluorescence in situ hybridization were conducted with samples from two humic reservoirs in order to examine how inorganic nutrients (N, P) affect free-living bacterioplankton phylogenetic groups and subsequently the quality of dissolved organic matter (DOM). The experiments were complemented by analyses of the empirical relationships between the targeted bacteria, nutrients, DOM and grazers. The ratio of absorbance of waters (A) at 250 and 365 nm (A(250 nm):A(365 nm)),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 52 publications
5
32
1
Order By: Relevance
“…However, the fact that Planctomycetes abundances increase during or after phytoplankton blooms (which are known to release large amounts of carbon, nitrogen, and phosphorus) indicates that dissolved organic matter (DOM) and inorganic-nutrient availability are key factors enhancing Planctomycetes growth and suggests that their low abundance might also be an indication that they are poor competitors for some nutrients. An experimental study has also shown strong increases in the abundance of pelagic Planctomycetes (estimated by fluorescent in situ hybridization) following additions of inorganic nitrogen and phosphorus, alone or in combination, in the absence of grazers (6). In many cases in that study, the increase in Planctomycetes abundances was greater than (N addition) or similar to those of dominant groups, such as betaproteobacteria (6).…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…However, the fact that Planctomycetes abundances increase during or after phytoplankton blooms (which are known to release large amounts of carbon, nitrogen, and phosphorus) indicates that dissolved organic matter (DOM) and inorganic-nutrient availability are key factors enhancing Planctomycetes growth and suggests that their low abundance might also be an indication that they are poor competitors for some nutrients. An experimental study has also shown strong increases in the abundance of pelagic Planctomycetes (estimated by fluorescent in situ hybridization) following additions of inorganic nitrogen and phosphorus, alone or in combination, in the absence of grazers (6). In many cases in that study, the increase in Planctomycetes abundances was greater than (N addition) or similar to those of dominant groups, such as betaproteobacteria (6).…”
mentioning
confidence: 76%
“…In aquatic ecosystems, they represent between 0 and 11% of planktonic prokaryotic communities (3,4,5,6,7). Despite this low abundance, the role of Planctomycetes in aquatic ecosystem functioning is increasingly recognized, given their involvement in nitrogen and carbon cycling (6,8,9,10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4). Many studies have reported high relative abundance of Bacteroidetes or Planctomycetes following algal blooms [56][57][58][59][60]. Both phyla are known to be present and attached to aggregates, and they have various extracellular enzymes that can degrade complex organic molecules and give a competitive advantage with regards to other microbial groups [61][62][63].…”
Section: Discussionmentioning
confidence: 99%